Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/710
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Scheme for Counting Linear Extensions

Abstract: Counting the linear extensions of a given partial order not only has several applications in artificial intelligence but also represents a hard problem that challenges modern paradigms for approximate counting. Recently, Talvitie et al. (AAAI 2018) showed that an exponential time scheme beats the fastest known polynomial time schemes in practice, even if allowing hours of running time. Here, we present a novel scheme, relaxation Tootsie Pop, which in our experiments exhibits polynomial characteristics and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…If no explicit mapping is required, the agent attempts to learn the abstraction of the MPD, which are invariant even though actions and state variables change [36], [37]. Another approach is to learn inter-task mapping automatically [38], [39] using novel mapping learning methods. Applying heuristics in transfer learning is proven to have reasonable acceleration in target task learning.…”
Section: Recent and Relevant Workmentioning
confidence: 99%
“…If no explicit mapping is required, the agent attempts to learn the abstraction of the MPD, which are invariant even though actions and state variables change [36], [37]. Another approach is to learn inter-task mapping automatically [38], [39] using novel mapping learning methods. Applying heuristics in transfer learning is proven to have reasonable acceleration in target task learning.…”
Section: Recent and Relevant Workmentioning
confidence: 99%
“…Several fully polynomialtime randomized schemes have also been designed, which are based on Markov chain Monte Carlo (MCMC) schemes such as the telescopic product estimator and the Tootsie Pop algorithm. Recently, [43] present a novel scheme called relaxation Tootsie Pop, and showed that it is superior to all previous schemes (including the scheme of encoding the problem into #SAT).…”
Section: Counting Linear Extensionsmentioning
confidence: 99%
“…From a practical viewpoint, however, (asymptotic) worst-case bounds are only of secondary interest: it would suffice that an algorithm outputs an estimate that, with high probability, is guaranteed to be within a small relative error of the exact value-no good upper bound for the running time is required a priori; it is typically satisfactory that the algorithm runs fast on the instances one encounters in practice. The artificial intelligence research community, in particular, has found this paradigm attractive for problems in various domains, including probabilistic inference [1,7], weighted model counting [12,11], network reliability [26], and counting linear extensions [35].…”
Section: Introductionmentioning
confidence: 99%